Serum hydroxycotinine was associated with chronic kidney disease (CKD): a cross-sectional study based on NHANES - Meng’en Zhu; Zhimin Bi; Yaoling Wang; Wei Li (Renal Failure)
Objective Smoking has been suggested as a modifiable and cardiovascular risk factor for chronic kidney disease (CKD). Although long-term smoking has been associated with CKD, the potential relationship between its metabolite hydroxycotinine and CKD has not been clarified.Methods A total of 8,544 participants aged 20 years and above from the National Health and Nutrition Examination Survey (NHANES) 2017 - March 2020 were enrolled in our study. CKD was defined by estimated glomerular filtration rate (eGFR) < 60 mL/(min*1.73 m2). Serum hydroxycotinine was measured by an isotope-dilution high-performance liquid chromatography/atmospheric pressure chemical ionization tandem mass spectrometric (ID HPLC-APCI MS/MS) method with a lower limit of detections (LLOD) at 0.015 ng/mL. The non-linear relationship was explored with restricted cubic splines (RCS). Pearson’s correlation coefficient and a multivariate logistic regression model were used for correlation analysis.Results Serum hydroxycotinine and eGFR were negatively correlated in both non-CKD group (r= −0.05, p < 0.001) and CKD group (r= −0.04, p < 0.001). After serum hydoxycotinine dichotominzed with LLOD, serum hydroxycotinine ≥ 0.015 ng/mL was negatively correlated with eGFR not only in non-CKD group (r = −0.05, p < 0.001) but also in CKD group (r = −0.09, p < 0.001). After adjusting for comprehensive confounders, results from the multivariate logistic regression analysis showed that participants with serum hydroxycotinine ≥ 0.015 ng/mL had increased odds of CKD (OR = 1.505, p < 0.001).Conclusions Serum hydroxycotinine might be positively associated with CKD. Further study is warranted to find the right concentration of hydroxycotinine to measure the CKD.